Enhancing creative teaching behaviour of vocational school teachers: structural equation modelling analysis - Tamrin, Agusti G.; Triyono, Mochamad Bruri; Saputro, Ida Nugroho; Sucipto, Taufiq Lilo Adi; Asnur, Lise (Intelektual Pustaka Media Utama, 2025)
Creative teaching behavior (CTB) is an innovative and creative teaching approach that is relevant in facing the dynamics of vocational education, which continues to develop, especially to produce creative students. Many studies examine the important role of CTB. However, limited information still discusses how to improve CTB by involving important factors such as creative climate, school support, and creative teaching self-efficacy. This study involved 400 teachers from 25 vocational high schools in civil engineering in Central Java Province, and data analysis using the structural equation modelling (SEM) (Smart-PLS) method. The study results revealed that CTB was proven to be influenced positively and significantly by school support and creative teaching self-efficacy. Also, creative teaching self-efficacy partially mediates the effect of creative climate and school support on CTB. The results of this study provide important implications for vocational school teachers to develop creative teaching skills in schools. Building a creative culture in schools, proactive school support and increasing teacher self-confidence are essential steps in creating a dynamic and innovative learning environment in vocational schools.